Investigation of LaxSr1−xCoyM1−yO3−δ (M = Mn, Fe) perovskite materials as thermochemical energy storage media. (August 2015) - Babiniec, Sean M.; Coker, Eric N.; Miller, James E.; Ambrosini, Andrea
Highlights: The synthesis and crystal structure of 37 LSCM/F materials are presented in detail. The redox propensity of each material is evaluated by thermogravimetric analysis. Large redox activities were observed in samples with cubic or tetragonal structure. Equilibrium thermogravimetric analysis is used to extract thermodynamic parameters. The top material candidate exhibits a reduction enthalpy of 250 kJ/kg. Abstract: Materials in the La x Sr1− x Co y Mn1− y O3− δ (LSCM) and La x Sr1− x Co y Fe1− y O3− δ (LSCF) families are candidates for high-temperature thermochemical energy storage due to their facility for cyclic endothermic reduction and exothermic oxidation. A set of 16 LSCM and 21 LSCF compositions were synthesized by a modified Pechini method and characterized by powder X-ray diffraction and thermogravimetric analysis. All materials were found to be various symmetries of the perovskite phase. LSCM was indexed as tetragonal, cubic, rhombohedral, or orthorhombic as a function of increased lanthanum content. For LSCF, compositions containing low lanthanum content were indexed as cubic while materials with high lanthanum content were indexed as rhombohedral. An initial screening of redox activity was completed by thermogravimetric analysis for each composition. The top three compositions with the greatest recoverable redox capacity for each family were further characterized in equilibrium thermogravimetric experiments over a range of temperatures and oxygen partial pressures. These equilibrium experiments allowed the extraction of thermodynamic parameters for LSCM and LSCF compositions operated in thermochemical energy storage conditions .